IMPLEMENTASI PERATURAN MENTERI PENDIDIKAN, KEBUDAYAAN, RISET, DAN TEKNOLOGI NOMOR 39 TAHUN 2021 TENTANG INTEGRITAS AKADEMIK DALAM MENGHASILKAN KARYA ILMIAH DI UNIVERSITAS RIAU - Handika, Yoga; HB, Gusliana; Haryono, Dodi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Higher education institutions in realizing the implementation of education,research and community service, always uphold the values and norms in order to createa conducive academic climate. Guidance regarding academic integrity is an effort madeby higher education institutions in order to shape the character of academicians withintegrity, and maintain academic culture in higher education. Based on Article 5 ofPermendikbudristek Number 39 of 2021, it is stated that the guidance of academicintegrity values is carried out, one of which is through the establishment of regulationsregarding academic integrity in producing scientific works. The purpose of writing thisthesis is; First, to find out the Implementation of Permendikbudristek Number 39 of 2021concerning Academic Integrity in Producing Scientific Works at the University of Riau.Second, to find out the inhibiting factors and efforts to overcome obstacles to theImplementation of Permendikbudristek Number 39 of 2021 concerning AcademicIntegrity in Producing Scientific Works at the University of Riau.This type of research is empirical legal research, namely a research approach thatemphasizes legal aspects related to the main problem to be discussed, linked to the realityin the field. This research was conducted at the University of Riau. From the results ofthe problem research, there are two main things that can be concluded. First, theimplementation of Permendikbudristek Number 39 of 2021 at the University of Riau hasnot been optimally implemented. The implementation of academic integrity in producingscientific works at UNRI in the process of its implementation is still guided by the oldregulations and the new regulations are still in draft form which have not been stipulatedin the Chancellor's Regulation. Second, the technical regulations related to academicintegrity in producing scientific works with the Chancellor's Regulation have not beenstipulated due to the busyness of the UNRI apparatus and leadership. And the effortsmade to overcome this are that the Senate has written to the parties involved in thepreparation of the draft to immediately complete the formulation of the regulations, willimmediately optimize massive and sustainable socializationKeywords: Academic Integrity – Scientific Work – University of Riau –Plagiarism